Knowledge, experiences, and perceptions relating to obesity management among primary care physicians in the Lazio Region, Italy - Guglielmi, Valeria; Capoccia, Danila; Russo, Benedetta; Lubrano, Carla; Mariani, Stefania; Poggiogalle, Eleonora; Furia, Giuseppe; Alizadeh, Aurora Heidar; Patrizi, Cristina; Sapienza, Martina; Damiani, Gianfranco; Tarsitano, Maria Grazia; et al. (Frontiers in Endocrinology, 2023)
Background: Primary care providers (PCPs) play an essential role in obesity care as they represent the first contact for patients seeking weight loss interventions.Objective: This study explored the knowledge, experiences, and perceptions of PCPs in the Lazio Region of Italy in the management of obesity.Design and Subjects: We conducted an anonymous survey delivered from March to July 2022 via the newsletter of Rome Provincial Order of Physicians and Dentists and at the annual meeting of the regional section of the Italian Obesity Society.Approach: The survey consisted of 24 closed-ended questions grouped into 5 sections: sociodemographic and work information; assessment of obesity; management of obesity; connections with regional Centres for Obesity Management; attitudes towards obesity. Key Results: A total of 92 PCPs accessed the survey. Of those, 2.2% were excluded because they did not see any patients with obesity. A total of 68 PCPs (75.6%) had complete questionnaires and were included in this analysis. All participants reported asking their patients about their eating habits, lifestyle, and clinical complications at the first assessment. Body weight and blood pressure were measured by 98.5% of participants and 82% calculate body mass index (BMI), while a small proportion of PCPs analysed body composition and fat distribution. Over 80% prescribed laboratory tests and ECG. Approximately 40% of PCPs did not refer patients for nutritional counselling, and most prescribed a low-calorie diet. Sixty-three percent referred patients to an endocrinologist, 48.5% to a psychotherapist, and a minority to specialists for obesity complications. Twenty-three percent prescribed anti-obesity medications and 46.5% referred patients for bariatric surgery only in severe cases. Ninety-one percent stated that obesity is "a complex and multifactorial disease" and 7.4% considered obesity to be secondary to other conditions. Conclusions: Despite most PCPs adopt a correct approach to manage patients with obesity, many aspects could be improved to ensure optimal and multidisciplinary management.